QUALITATIVE ANALYSIS OF ANTIMICROBIAL COMPOUND BY HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHY METHOD - BERNICE SHARON, S. FEBINA; KALIDASS, S.; DANIEL, RACHEL REGI (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: To perform qualitative analysis of antimicrobial compound by High performance thin layer chromatography method. Methods: Streptomyces sp. 2011 (JF751041) had been isolated from the marine coastal soil of Marina beach, Chennai. Streptomyces sp. 2011 was found to be the most potent isolate and the solvent ethyl acetate was used for extracting the bioactive compounds. The bioactive compounds were separated by solvent extraction and phase separation method. The ethyl acetate solvent containing the extract was subjected to High Performance Thin Layer Chromatography to find out the presence of ester, quinone, macrolide and terpenoids. Results: Ten bacterial and two fungal pathogens were challenged against the crude extract. Salmonella paratyphi, Pseudomonas aeruginosa, Bacillus subtilis were resistant to the extract where as Escherichia coli and Lactobacillus acidophilus were less sensitive. All the other five bacteria and two fungi were showing excellent inhibition diameter. Clotrimazole, Ampicillin and Tetracycline were used as positive controls where as ethyl acetate solvent were used as negative control. The results of High Performance Thin Layer Chromatography proved the presence of ester, macrolide and terpenoids. Conclusion: The results of the antimicrobial activity of Streptomyces sp. 2011 and the presence of bioactive compounds like ester, terpenoid and macrolide clearly proved that the marine soil of Marina beach is a good harbor for isolating novel varieties of antagonistic Streptomyces sp. and for producing broad spectrum antibiotics. Key words: Streptomyces sp. 2011 (JF751041), HPTLC, Antibiotics, Macrolide, Terpenoid, Quinone, Ester, Antimicrobial